Unusual Spurts of Rosacea Like Dermatoses, Posing a Diagnostic Dilemma During Covid-19 Pandemic: A Cross-Sectional, Observational Study From a Tertiary Care Centre - Gautam Kumar Singh; Barnali Mitra; Anuj Bhatnagar; Debdeep Mitra; Krishna Talukdar; Pankaj Das; Chetan Patil; Sunmeet Sandhu; Anwita Sinha; Teghveer Singh (Wolters Kluwer Medknow Publications, 2021)
Background: The gradual opening of healthcare system since second week of May 2020 following lockdown imposed due to corona virus pandemic saw spurts of cases of unexplained central facial dermatoses in subset of previously healthy people. The aim of the study was to find out the cause and establish the definitive diagnosis of unusual occurrence of facial dermatoses on previously healthy people so that an appropriate management can be offered to the patients. Materials and Methods: It was a cross-sectional, observational study carried during May 15 to July 15, 2020 at a tertiary dermatology center. All cases presented with erythema on face and papular or pustular lesions on central facial area of not more than 2 months of duration were included in the study. Results: Total 81 patients visited skin OPD with facial dermatoses of various types during this period, out of which 21 patients fulfilled the inclusion criteria. This was 0.72% (21/2900) of total skin OPD of the 2 months. All the patients had been using face masks during this period of symptoms due to the ongoing coronavirus situation. Dermatological examination revealed only erythema on the central area of face (n = 10), erythema and few papules (n = 3), erythmatous papules and pustules (n = 5), and erythematous papules, pustules, and telengiectasia (n = 3). All the skin biopsies showed predominantly epithelioid cells, noncaseating granuloma with a variable degree of infiltrate. Conclusion: There has been a definite change in the lifestyle due to the current Covid-19 pandemic. People are compulsorily using face masks to avoid the spread of Covid-19 infection. This change in behavior has brought out a surge of rosacea like lesions on the covered area of face. Partly, it can be explained by change in innate immunity due to excessive sweating and change in microenvironment of skin.